Effects of stocking density on growth and survival of tilapia cultured in biofloc technology system in brackish water - Thanh, Nguyen Xuan; Cuong, Le Duc; Hiep, Le Minh; Tuyet, Dao Thi Anh (Vietnam Journal of Marine Science and Technology, 2020)
This study examined the effect of stocking density on growth and survival of tilapia cultured in biofloc technology system. Three different stocking densities cultured in biofloc technology were 6 fish/m3, 8 fish/m3 and 10 fish/m3 for 86 days in triplicate for each treatment. The stocking density of the control lot was 3 fish/m3 cultured without biofloc technology. Initial stocking weight ranged from 2–3 g/fish. The water quality parameters were monitored and regulated in the suitable ranges for biofloc technology and for the growth and development of tilapia. The results showed that specific growth rate of fish cultured at a density of 6 fish/m3 was higher than that in the treatments of 8 fish/m3 and 10 fish/m3 with the average values of 5.72%; 5.62% and 5.43%, respectively, and the specific growth rate of fish in the control treatment was 5.71%. Daily growth rate of fish cultured at a density of 6 fish/m3 was higher than that cultured at densities of 8 fish/m3 and 10 fish/m3 with average values of 3.19 g/day, 2.98 g/day, and 2.55 g/day, respectively; and the daily growth rate of the control treatment was 3.27 g/day. Survival rate of tilapia cultured at densities of 6 fish/m3 and 8 fish/m3 was 100%, whereas survival rate of tilapia cultured at a density of 10 fish/m3 was 95.75%, and it was 88.9% for the control lot. The research results provide a scientific basis to propose tilapia culture technique in biofloc technology in brackish water, with the density of 6–8 fish/m3.